Penerapan Model Pembelajaran Think Pair Share Untuk Meningkatkan Hasil Belajar Matematika Siswa Kelas 3 SDN 009 Rambah Samo - Suprapti Suprapti (Jurnal Absis: Jurnal Pendidikan Matematika dan Matematika, 2019)
This research background was the low learning outcomes of students in grade 3 at SDN 009 Rambah Samo. The purpose of this study is to improve student mathematics learning outcomes through the application of Think Pair Share (TPS) learning. The type of research conducted is classroom action research. The study implemented in two cycles, with three meetings in each period. Classroom action research procedures carried out include planning, implementing, observing, and reflecting. The instrument used was a test of learning outcomes and an observation sheet of teacher and student activities. The results showed that the average student learning outcomes increased from 52.95 in the initial data to 69.86 in the first cycle with a percentage increase of 31.94% and 84.17 in the second cycle with an increase from cycle 1 of 20, 7%. Individual completeness obtained from the initial data up to cycle 2 was 43.47%, 65.21%, and 78.26%, respectively. So it can be concluded that the application of the TPS learning model can improve mathematics learning outcomes of students in grade 3 at SDN 009 Rambah Samo.